Digital games in Mathematics teaching and learning processes: A focus on high school (Research, Society and Development, 2022)
Digital games gain, every day, more space in contemporary society. Educational establishments already demonstrate this concern to meet this new educational demand, seeking to insert games into their environments. Given this reality, the present work presents a Systematic Literature Review (RSL) about the use of digital games in mathematics teaching with an application aimed at high school students. Five databases were used to obtain the RSL studies, namely: Google Scholar, ERIC, CAPES Periodicals, Gale Academic OneFile and JSTOR. According to the results obtained, it is clear that the application of games to high school students in the discipline of mathematics is still a little explored field, there are demands for more research and studies in this area. On the other hand, in the articles analyzed in this RSL, it was observed that all of them report the great potential that digital games can bring to high school students in terms of participation, involvement and engagement in their mathematical learning process.